Jugendliche der "Roten Falken" beim Bauen einer Trage (?), um 1940
politischer Rahmen;politisches Leben (allgemein);politische Bewegung politischer Rahmen;politisches Leben (allgemein);politische Bewegung;Jugendbewegung